Powdered garlic in the alternative feeding of broiler chickens - Carrijo, Alfredo Sampaio; Madeira, Luciene Aparecida; Sartori, José Roberto; Pezzato, Antonio Celso; Gonçalves, Jane Cristina; da Cruz, Valquíria Cação; Kuibida, Karin Virgínia; Pinheiro, Daniela Felipe (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The objective of this work was to evaluate the inclusion of powered garlic (Allium Sativum) in diets of broiler chickens and the effect of this inclusion on the performance, carcass yield and parts, organ weights, serum cholesterol and triacilglycerols levels, as well as intestinal morphometry. Seven hundred and twenty male Cobb chicks one-day-old were distributed in randomized blocks with six treatments: diet without growth promoter and without anticoccidial (GP+AC) and with 0.00, 0.25, 0.50, 0.75 and 1.00% of powered garlic, and diet with GP+AC, with four replications of 30 chickens each. Chickens were reared up to 42 days old. Weight, weight gain, feed intake, feed conversion and mortality were obtained at 21 and 42 days. At the 42nd, 20 chickens per treatment were slaughtered in order to determine carcass yield and other 4 chickens per treatment were used to estimate organ weights and intestinal morphology. Blood of 8 chickens per treatment was collected to determine cholesterol and triacilglycerols. For the birds feeding on the diet without growth promoter and without anticoccidial, the inclusion up to 1.00% of powered garlic in the diet improved feed conversion and did not alter carcass yield and parts, organ weights, intestinal mucous or influenced the serum levels of cholesterol and triacilglycerols. The garlic did not replace efficiently the antibiotic.